Blood lead levels and associated factors among children residents of a callao district - Morales, Juan (2018)
Objectives. Classifying blood lead levels and identifying the factors associated with elevated blood lead levels in children living in a district of Callao. Materials and methods. Transversal descriptive study. The study population was composed of children of both sexes from 1 to 13 years old; the data collection was conducted between March and April 2017. Results. The 310 children studied presented an average blood lead level of 8.59 μg/dL, while the median (P50) blood lead level was higher in males (p=0.008). Blood lead levels in 18.1% of the study population (n=56) were <5 μg/dL; in 54.5% (n=169) levels ranged between 5 and 10 μg/dL, whereas 27.4% (n=85) reported blood lead levels of ≥10 μg/dL furthermore, blood lead levels were significantly different between genders (p=0.007), while significantly more children under 10 years of age (p=0.008) and whose parents did not receive any training and/or education regarding the risks of lead exposure (p<0.001) reported blood lead levels of ≥10 μg/dL. Statistically significant risk factors linked to elevated blood lead levels included, residence with dirt floor (OR:2.92, 95% CI: 1.26-6.78), ingesting of dirt (OR:1.76, 95% CI: 1.02-3.07), biting or sucking of pencils (OR:1.86; IC95%: 1.12-3.10) and biting or sucking of toys (OR:1.97, IC95%: 1.16-3.33). Conclusions. A high proportion of children showed elevated blood lead levels, with associated factors either related or not to the home. Certainly, it is imperative to take actions linked to public health policies, adopting the new thresholds considered in international health regulations.